Coronavirus Disease 2019 (COVID-19): Current Situation and Therapeutic Options - Singh V.; Mishra V. (My University, 2025)
Coronavirus disease 2019 (COVID-19) is defined as an illness caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). COVID-19 was first reported in the Wuhan, China, in late December, 2019. The World Health Organization (WHO) declared COVID-19 a global emergency on March 11, 2020. COVID-19 was rapidly transmitted and caused infection in 21,294,845 people and 761,779 deaths in more than 213 countries worldwide till August 16, 2020. United States of America (USA), Brazil, India, Russia Federation, Peru, Mexico, Colombia, Spain, France, Italy, Germany, and United Kingdom (UK) stand top COVID-19 affected countries in the world. The high transmission rate of COVID-19 might be due to large viral incubation time (2-14 days) and some modifications in the spike glycoprotein. Currently, effective drugs or vaccines are not developed for the treatment of novel coronavirus. However, few antibiotics like hydroxychloroquine and remdesivir have been currently used for the treatment of COVID-19 infection. Several collaboratives are working together for developing an effective and safe vaccine against COVID-19 and few vaccines are under clinical trial. Scientists are also working on plasma therapy and monoclonal antibodies. Nowadays, plasma therapy is considered the most effective treatment against COVID-19 and some promising results have been achieved. This review focuses on several therapeutic options for COVID-19, such as anti-viral drugs, vaccines, plasma therapy, and monoclonal antibodies. This review also covers the current situations of COVID-19 in the world. This review is about COVID-19, which will be beneficial to researchers for the development of potential treatment against it. © 2021 Bentham Science Publishers.